Acuity - Universitas Advent Indonesia (Universitas Advent Indonesia, 2016)
Research journal for the Teaching of English, Literature & Culture. It publishes research-based articles, reviews, and poems, which reflect on every aspect of English teaching.
Keywords: English language : Study and teaching : Periodicals; English language : Study and teaching : Indonesia : Periodicals; English language : Study and teaching : Indonesian speakers : Periodicals; English literature : Study and teaching : Indonesia : Periodicals; English language : Study and teaching : Indonesian speakers; English language : Study and teaching; English literature : Study and teaching; Indonesia